The Effect of Work Placement and Work Discipline on Employee Performance Through Job Satisfaction Case Study of the Surya Kencana Lumajang Savings and Loan Cooperative - Firli Adri Ridhotama; Hary Sulaksono; Tamriatin Hidayah (ABM: International Journal of Administration, Business and Management, 2022)
This study aims to analyze the effect of work placement and work discipline on employee performance through case study job satisfaction at the Surya Kencana Lumajang Savings and Loan Cooperative. This type of research is included in the type of quantitative research. The sample used was 40 respondents with a saturated sample technique. The data analysis method used is path analysis. The results showed that job placement had a significant effect on job satisfaction, work discipline had no significant effect on job satisfaction, job placement had no effect on performance, work discipline had no effect on performance, job satisfaction had an effect on employee performance, job placement had an effect on performance through satisfaction. work, work discipline has no effect on performance through job satisfaction